Extracts of Amazonian Fungi With Larvicidal Activities Against Aedes aegypti - de Oliveira, Marta Rodrigues; Katak, Ricardo de Melo; da Silva, Gilvan Ferreira; Marinotti, Osvaldo; Terenius, Olle; Tadei, Wanderli Pedro; de Souza, Afonso Duarte Leão; de Souza, Antonia Queiroz Lima (Frontiers in Microbiology, 2021)
The global increase in diseases transmitted by the vector Aedes aegypti, new and re-emerging, underscores the need for alternative and more effective methods of controlling mosquitoes. Our aim was to identify fungal strains from the Amazon rain forest that produce metabolites with larvicidal activity against Aedes aegypti. Thirty-six fungal strains belonging to 23 different genera of fungi, isolated from water samples collected in the state of Amazonas, Brazil were cultivated. The liquid medium was separated from the mycelium by filtration. Medium fractions were extracted with ethyl acetate and isopropanol 9:1 volume:volume, and the mycelia with ethyl acetate and methanol 1:1. The extracts were vacuum dried and the larvicidal activity was evaluated in selective bioassays containing 500 µg/ml of the dried fungal extracts. Larval mortality was evaluated up to 72 h. None of the mycelium extracts showed larvicidal activity greater than 50% at 72 h. In contrast, 15 culture medium extracts had larvicidal activity equal to or greater than 50% and eight killed more than 90% of the larvae within 72 h. These eight extracts from fungi belonging to seven different genera (Aspergillus, Cladosporium, Trichoderma, Diaporthe, Albifimbria, Emmia and Serocladium) were selected for the determination of LC50 and LC90. Albifimbria lateralis (1160) medium extracts presented the lowest LC50 value (0.268 µg/ml) after 24 h exposure. Diaporthe ueckerae (1203) medium extracts presented the lowest value of LC90 (2.928 µg/ml) at 24 h, the lowest values of LC50 (0.108 µg/ml) and LC90 (0.894 µg/ml) at 48 h and also at 72 h (LC50 = 0.062 µg/ml and LC90 = 0.476 µg/ml). Extracts from Al. lateralis (1160) and D. ueckerae (1203) showed potential for developing new, naturally derived products, to be applied in integrated vector management programs against Ae. aegypti.